BIOMIMETIC METHOD OF CALCIUM HYDROXYAPATITE SYNTHESIS - Jokanović, V.; Čolović, B. (Journal of Engineering & Processing Management, 2009)
Calcium hydroxyapatite (CHA) has been synthesized biomimetically using simulated body fluid (SBF) alone and in combination with Fetal Calf Serum (FCS) and Eagle’s Minimum Essential Medium (EMEM). Chemical composition of the used SBF is like composition of human plasma, with small differencies in some ions concentrations, and pH value was adjusted to 7.4, that corresponds to pH of physiological media. As substrate for biomimetic deposition of apatite, thin films of silica, deposited on steel plates, were used. The analysis of phases obtained on the surface of SiO2 films after different periods of CHA nucleation, was done by FTIR-ATR method. SEM investigations pointed out the mechanism of nucleation, while combination of the method of measurement of film mass and BET method showed that thickness of nucleated CHA films depend on time of sample soaking in SBF.